2014
DOI: 10.48550/arxiv.1412.2126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A general method for the resummation of event-shape distributions in e^+e^- annihilation

Abstract: We present a novel method for resummation of event shapes to next-to-next-to-leadinglogarithmic (NNLL) accuracy. We discuss the technique and describe its implementation in a numerical program in the case of e + e − collisions where the resummed prediction is matched to NNLO. We reproduce all the existing predictions and present new results for oblateness and thrust major. Contents 1 Introduction 2 Review of NLL resummation 3 NNLL resummation 3.1 Logarithmic counting for the resolved real emissions 3.2 Structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(121 citation statements)
references
References 61 publications
(106 reference statements)
3
118
0
Order By: Relevance
“…Very recently, a different approach using the coherent branching formalism of refs. [25,26] has been proposed in ref. [24], which is not based on a factorization theorem or solving the q T evolution equations.…”
Section: Coherent Branching Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, a different approach using the coherent branching formalism of refs. [25,26] has been proposed in ref. [24], which is not based on a factorization theorem or solving the q T evolution equations.…”
Section: Coherent Branching Formalismmentioning
confidence: 99%
“…Recently, ref. [24] obtained the resummation in momentum space based on the coherent branching formalism [25,26] rather than solving the evolution equations associated with a factorization theorem. They showed that the spurious divergences are avoided by expanding around the transverse momentum of the hardest emission instead of q T .…”
Section: Introductionmentioning
confidence: 99%
“…e.g. [91][92][93][94] for the combination of fixed-order and resummed predictions for event shapes in e + e − annihilation. As a consequence, we therefore impose a small cut-off y 0 = 10 −5 on all linear distributions and y 0 = e −10 on logarithmically binned distributions in practice.…”
Section: Numerical Set-up and Scale-variation Prescriptionmentioning
confidence: 99%
“…Fig. 2 concentrates on a medium-p T,jet bin, p T,jet ∈ [120,150] GeV, for both the Z+jet and the central dijet selection and Fig. 3 shows the corresponding results for the highest p T,jet interval, p T,jet ∈ [1000, 4000] GeV.…”
Section: Transfer Matrices For Jet-angularity Observablesmentioning
confidence: 99%
“…4. We select jets with R = 0.8 and p T,jet ∈ [120,150] GeV in central dijet events and measure the jet width, λ 1 1 , either on ungroomed jets (left plot) or on groomed jets (right plot). At hadron level, the jet width is measured on charged particles only.…”
Section: Transfer Matrices For Jet-angularity Observablesmentioning
confidence: 99%